Potential Screening Relationship Between Lipid Profil and Preeclampsia Review - Fitriani, Fitriani; Sari, Yuni (Institute Of Computer Science (IOCS), 2025)
Per-eclampsia and eclampsia are among the leading causes of maternal perinatal mortality and morbidity worldwide. Lipid Profile examination screening is one of the potential screening relationships between the incidence of pre-eclampsia in pregnant women. This study aims to determine the difference in average lipid profile (total cholesterol, LDL cholesterol, HDL cholesterol, and triglycerides) between per-eclamptia pregnant women and normal pregnant women. The research method used an observational study design with a case-control study approach. The population is all pregnant women with pre-eclampsia and normal pregnant women who seek outpatient treatment and have been hospitalized at RSUZA Banda Aceh from May to November 2024. The sample in this study consisted of 2 unpaired groups, so the number of samples of each group was 11 people. Data collection was carried out by clinical laboratory examination. Data analysis used is descriptive analysis and inferential analysis using independent t-test and chi-square test. The results showed there was a difference in average total cholesterol (p=0.000) and LDL cholesterol (p=0.006) between the pre-eclampsia pregnant women group and normal pregnant women, and there is no difference in the average levels of HDL cholesterol (p=0.102) and triglycerides (p=0.679). It is recommended that pregnant women conduct routine lipid profile checks to detect the risk of pre-eclampsia in pregnancy.